Catalyzing native forest regeneration on degraded tropical lands - Parrotta, J.A.; Turnbull, J.W.; Jones, N. (1997)
Forest clearing, forest degradation through human disturbance, and the deterioration of land productivity due to inappropriate agricultural practices is a major problem in the tropics. Restoration of ecosystem health and productivity has generally relied on abandonment of land and subsequent natural for succession. In recent years there has been consideration of management options to accelerate recovery and restore productivity, biodiversity and other values. The use of tree plantations to catalyze restoration of degraded forests and lands in the tropics was addressed at a symposium in Washington DC in June 1996. The conclusions and suggestions for future research to develop appropriate management options are reported. There is strong evidence that plantations can facilitate forest succession in their understories through modification of both physical and biological site conditions. Changes in light, temperature and moisture at the soil surface enable germination and growth of seeds transported to the site by wildlife and other vectors from adjacent forest remnants. Development and design of management options to assist this process are required, taking into account socio-economic realities, development priorities and conservation goals.